Modeling of a device for conducting experiments under low reactor neutron fluence rate conditions; Nuclear Energy and Technology; Vol. 11, iss. 2 - Veretennikov D. G. Dmitry Gennadjevich; Abouellail A. F. A. Abdelmeguid Fathy Ahmed; Ali A. H. Ahmed; Bedenko S. V. Sergey Vladimirovich (2025, 2025)
Title screen